Report of the International Regulatory Forum on Human Cell Therapy and Gene Therapy Products. Issue 5 (September 2016) - Hayakawa, Takao; Harris, Ian; Joung, Jeewon; Kanai, Nobuo; Kawamata, Shin; Kellathur, Srinivasan; Koga, Junichi; Lin, Yi-Chu; Maruyama, Yoshiaki; McBlane, James; Nishimura, Takuya; Renner, Matthias; et al.
Abstract: The development of human cell therapy and gene therapy products has progressed internationally. Efforts have been made to address regulatory challenges in the evaluation of quality, efficacy, and safety of the products. In this forum, updates on the specific challenges in quality, efficacy, and safety of products in the view of international development were shared through the exchange of information and opinions among experts from regulatory authorities, academic institutions, and industry practitioners. Sessions identified specific/critical points to consider for the evaluation of human cell therapy and gene therapy products that are different from conventional biological products; common approaches and practices among regulatory regions were also shared. Certain elements of current international guidelines might not be appropriate to be applied to these products. Further, international discussion on the concept of potency and in vivo tumorigenicity studies, among others, is needed. This forum concluded that the continued collective actions are expected to promote international convergence of regulatory approaches of the products. The Pharmaceuticals and Medical Devices Agency and Japanese Society for Regenerative Medicine jointly convened the forum with support from the National Institutes of Biomedical Innovation, Health and Nutrition. Participants at the forum include 300 experts in and outside of Japan. Highlights: The forum identified the majority of regulatory approaches with high similarity across the regions. Potency may result in specific profiles for matrix approach, will need a new definition for hCTPs. Needs and limitations of in vivo tumorigenicity studies be recognized, and consensus, pursued. Risk-based flexibility for requirements be promoted, considering complexity and variety of hCTPs. Scientific alignment among authorities through international fora should be continued.